2021
DOI: 10.3390/molecules26175422
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption/Desorption Behaviors and SERS Chemical Enhancement of 6-Mercaptopurine on a Nanostructured Gold Surface: The Au20 Cluster Model

Abstract: Computational approaches are employed to elucidate the binding mechanism and the SERS phenomenon of 6-mercaptopurine (6MP) adsorbed on the tetrahedral Au20 cluster as a simple model for a nanostructured gold surface. Computations are carried out in both vacuum and aqueous environments using a continuum model. In the gaseous phase and neutral conditions, interaction of 6MP with the gold cluster is mostly dominated by a covalent Au−S bond and partially stabilized by the Au⋅⋅⋅H−N coupling. However, in acidic solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…In recent decades, nanostructured materials have become more and more widely used as an efficient approach for the diagnosis and treatment of diseases. Of the popular inorganic nanostructures such as oxides and noble metals, , those consisting of gold (Au) particles have peaked special attention as they exhibit unique properties and distinct advantages . Indeed, gold nanoparticles (AuNPs) are highly compatible to a plenty of bimolecular systems and in particular they are much less toxic to human as compared to many other metals .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, nanostructured materials have become more and more widely used as an efficient approach for the diagnosis and treatment of diseases. Of the popular inorganic nanostructures such as oxides and noble metals, , those consisting of gold (Au) particles have peaked special attention as they exhibit unique properties and distinct advantages . Indeed, gold nanoparticles (AuNPs) are highly compatible to a plenty of bimolecular systems and in particular they are much less toxic to human as compared to many other metals .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, gold nanoparticles have been approved as appropriate materials for many essential applications in biomedicine, biosensors and imaging ( Bai et al, 2020 ; Bansal et al, 2020 ; Zhang et al, 2020 ). In this context, it is important to elucidate the interaction mechanism, as well as the binding nature, of the drug and gold nanoparticles ( Sotnikov et al, 2019 ; Taghizadeh et al, 2019 ; Nhat et al, 2020a ; Chen et al, 2021 ; Hang et al, 2021 ). It has been found that the interactions are mainly stabilized by a charge transfer from the electron-rich atoms of ligands to Au metals ( Nhat et al, 2020b ; Si et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their results displayed that the BNNT is a more suitable carrier rather than CNT for delivery of MCP. Adsorption of the MCP upon other nanocarriers has been studied such as Au 20 nanocluster [13], nanosheet [14], Fe-doped fullerene [15], silver/gold cluster [16], Si, Al and Ti doped C60 fullerenes [17].…”
Section: Introductionmentioning
confidence: 99%